The Effect of Cognitive Behavior Theraphy On Online Gaming Addiction In Adolescents - Indah Andriani Ansar; Fatmawati; Haerati (Comprehensive Health Care, 2021)
Adolescence is one of the transitional periods of human development, where a person cannot be called an adult but no longer a child. The biggest users of online games in Indonesia are teenagers, where for teenagers playing online games is not a strange thing. pleasure and fun when playing games causes feelings of helplessness or inability to stop playing online games, so that in the end it affects other activities that are usually done daily. Knowing the effect of cognitive behavior therapy on online game addiction in adolescents at SMAN 7 Bulukumba in 2020 ". The design in this study is quantitative using research design, pre and post control group design, the sample of this study was 34 respondents who were divided into 2 groups (experimental and control), where the experimental group was given cognitive behavior therapy and the control group as a comparison. . The results of the analysis using the paired T test statistical test with a level of confidence (α = 0.05). Based on the results of this test. It was found that the p value in the experimental group was 0.000 and the p value in the control group was 0.163. So Ho was rejected and Ha accepted. The conclusion of this study is that there is an effect of cognitive behavior therapy on online game addiction in adolescents at SMA Negeri 7 Bulukumba in 2020, researchers suggest that more attention is needed to adolescents who are addicted to online games so as not to cause harm in the future.